Jealousy, by itself, does not constitute a “base motive” (CIPEEX, 2025)
This paper examines whether jealousy, taken alone, can sustain the qualifying circumstance of a “base motive” under Article 121(2)(I) of the Brazilian Criminal Code and in which circumstances such feeling, although blameworthy, should be weighed merely as a factor of violent emotion. It aims to clarify the criteria for subsuming a base motive, distinguishing it from a “frivolous motive” and from situations in which the defendant’s emotional state impacts only sentencing. Methodologically, it adopts a doctrinal-normative approach grounded in case law that allows striking out manifestly unfounded qualifiers and emphasizes that the motive must be assessed by the Jury Court on the concrete facts. The findings indicate that jealousy does not automatically amount to baseness or frivolity; the qualifier requires proof of ignoble ends or other objectively reprehensible circumstances that heighten culpability. It concludes that, absent such additional elements, the qualifier should be removed for lack of factual support and jealousy treated as an emotional state to be weighed as provided by law, while the Jury Panel assesses the competing versions and the evidentiary context.
Keywords: jealousy; base motive; violent emotion; criminal law